Chinese International Students in the United States: The Interplay of Students’ Acculturative Stress, Academic Standing, and Quality of Life - Su, Zhaohui; McDonnell, Dean; Shi, Feng; Liang, Bin; Li, Xiaoshan; Wen, Jun; Cai, Yuyang; Xiang, Yu-Tao; Yang, Ling (Frontiers in Psychology, 2021)
Background Acculturation could cause grave health consequences in international students. However, there is a shortage of research into how acculturative stress might affect international students’ quality of life in light of their academic standing and experience. The lack of research is particularly pronounced among Chinese international students, representing the largest body of international students studying in the United States (U.S.). Thus, to bridge the research gap, this study aims to examine the interplay between international students’ acculturative stress, academic standing, and quality of life among a nationally representative sample of Chinese international students studying in the United States. Methods An online survey that gauges Chinese international students’ levels of acculturative stress, academic standing, and quality of life was developed. Over 350 higher education institutions across the United States were approached, including public universities, private universities, and community colleges, among which approximately 220 institutions responded positively and supported survey distribution. A total of 751 students completed the survey. Multiple regression analyses were carried out to examine the associations between students’ acculturative stress, academic standing, and quality of life. Results Findings reveal that acculturative stress negatively affects all four domains of Chinese international students’ quality of life, irrespective of their academic standing. Data analyses also show that compared to master’s and doctoral students, undergraduates experience the highest levels of acculturative stress. Furthermore, a significant difference emerged among undergraduate and doctoral international students’ acculturative stress levels, but not among undergraduate and master’s students, or master’s and doctoral students. Conclusion Our study found that, compared to master’s and doctoral students, undergraduates had more significant acculturative stress associated with lower levels of quality of life. This finding highlights the potentially positive role of academic experience – while acculturative stress deteriorates international students’ quality of life, students’ academic standing and experience could be the protective factor in the equation. Future research could further examine how universities and colleges can capitalize on their academic apparatuses and resources to improve international students’ academic performance and students’ acculturation experience and quality of life.